Correction: Superior upconversion fluorescence dopants for highly efficient deep-blue electroluminescent devices. Issue 7 (16th May 2016) - Chen, Yi-Hsiang; Lin, Chih-Chun; Huang, Min-Jie; Hung, Kevin; Wu, Yi-Ching; Lin, Wei-Chieh; Chen-Cheng, Ren-Wu; Lin, Hao-Wu; Cheng, Chien-Hong
Abstract : Correction for 'Superior upconversion fluorescence dopants for highly efficient deep-blue electroluminescent devices' by Yi-Hsiang Chen et al., Chem. Sci., 2016, DOI: ; Web:10.1039/c6sc00100a .